Relations of Iran and Arab Countries of Persian Gulf: Some Aspects - Yu. N. Zinin (Международная аналитика, 2016)
The article emphasizes some aspects of relations of Iran and six Arab countries of the Cooperation Council for the Arab States of the Gulf (GCC) established in 1981. The issue of Saudi-Iranian relations, which are facing persistent deterioration since Islamic Revolution in Iran in 1979, is examined in broad terms.Nowadays these relations are witnessing the lowest level since diplomatic ties between two countries were severed in 2016. Consequently both states for a number of years had been involving into internal conflicts in Syria, Iraq, Yemen and Lebanon.The article covers commercial, economic, political and other relations of Teheran with the rest of the GCC members and theirs perspectives. The author analyses the influence of sunni-shut factor on the policy of ruling elites in the region.